Assessing Conflict Resolution Skills: Tensions and Opportunities - Jull, Marnie (Imagining SoTL, 2026)
In graduate-level courses that include conflict resolution as a core component, assessing conflict-engagement competencies of mid-career professionals presents several challenges. Educators must identify which competencies to emphasize while designing assignments and assessments that respect the cultures, professional backgrounds, and neurodiverse learning profiles of learners. This reflective paper explores the tensions and opportunities that educators can encounter when designing assignments and assessments that move beyond surface-level evaluation towards fostering deeper, more adaptive capacities for conflict engagement. Framed through a practitioner-inquiry lens, it highlights assignments and assessments that can engage learners to identify and develop conflict competencies that are appropriate for their personal and professional contexts. In doing so, it positions assessment alongside conflict engagement as evolving, messy, iterative, and deeply human processes.